Emergency Room Evaluation and Recommendations and Risk Screening of Incident Major Neurocognitive Disorders in Older Females: Results of an Observational Population-Based Cohort Study - Beauchet, Olivier; Matskiv, Jacqueline; Launay, Cyrille P.; Rolland, Yves; Schott, Anne-Marie; Allali, Gilles (Frontiers in Aging Neuroscience, 2022)
Background “Emergency Room Evaluation and Recommendations” (ER2) risk levels (i.e., low, moderate and high) may be used to screen for major neurocognitive disorders (MNCD) in older emergency department users, as a high ER2 risk level is associated with MNCD diagnosis. This study aims to examine the association of ER2 risk levels with incident MNCD in community-dwelling older adults. Methods A total of 709 participants of the EPIDémiologie de l’OStéoporose (EPIDOS) study—an observational population-based cohort study—were recruited in Toulouse (France). ER2 low, moderate and high risk levels were determined at baseline. Incident MNCD and their type (i.e., Alzheimer’s disease (AD) vs. non-AD) were diagnosed after a 7-year follow-up period. Results The overall incidence of MNCD was 29.1%. A low ER2 risk level was associated with low incidence of MNCD [Hazard ratio (HR) = 0.71 with P = 0.018] and AD (HR = 0.56 with P = 0.003), whereas a high risk level, both individually and when combined with a moderate risk level, was associated with high incidence of MNCD (HR ≥ 1.40 with P ≤0.018) and AD (HR ≥ 1.80 with P ≤ 0.003). No association was found with incident non-AD. Conclusion ER2 risk levels were positively associated with incident MNCD in EPIDOS participants, suggesting that ER2 may be used for risk screening of MNCD in the older population.